Distinct evolution of ST11 KL64 Klebsiella pneumoniae in Taiwan - Li, Yia-Ting; Wang, Yao-Chen; Chen, Chih-Ming; Tang, Hui-Ling; Chen, Bo-Han; Teng, Ru-Hsiou; Chiou, Chien-Shun; Lu, Min-Chi; Lai, Yi-Chyi (Frontiers in Microbiology, 2023)
Carbapenem-resistant ST11_KL64 Klebsiella pneumoniae emerged as a significant public health concern in Taiwan, peaking between 2013 and 2015, with the majority of isolates exhibiting OXA-48 as the sole carbapenemase. In this study, we employed whole-genome sequencing to investigate the molecular underpinnings of ST11_KL64 isolates collected from 2013 to 2021. Phylogenomic analysis revealed a notable genetic divergence between the ST11_KL64 strains in Taiwan and those in China, suggesting an independent evolutionary trajectory. Our findings indicated that the ST11_KL64_Taiwan lineage originated from the ST11_KL64 lineage in Brazil, with recombination events leading to the integration of ICEKp11 and a 27-kb fragment at the tRNA ASN sites, shaping its unique genomic landscape.To further elucidate this unique sublineage, we examined the plasmid contents.In contrast to ST11_KL64_Brazil strains, which predominantly carried blaKPC-2, ST11_KL64_Taiwan strains exhibited the acquisition of an epidemic blaOXA-48carrying IncL plasmid. Additionally, ST11_KL64_Taiwan strains consistently harbored a multi-drug resistance IncC plasmid, along with a collection of gene clusters that conferred resistance to heavy metals and the phage shock protein system via various Inc-type plasmids. Although few, there were still rare ST11_KL64_Taiwan strains that have evolved into hypervirulent CRKP through the horizontal acquisition of pLVPK variants.Comprehensive characterization of the high-risk ST11_KL64 lineage in Taiwan not only sheds light on its epidemic success but also provides essential data for ongoing surveillance efforts aimed at tracking the spread and evolution of ST11_KL64 across different geographical regions. Understanding the molecular underpinnings of CRKP evolution is crucial for developing effective strategies to combat its emergence and dissemination.